Cosmopolitanism in Mexican visual culture - Fernández, María, 1956- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2013)
Viewing four centuries of art and architecture anew through the lens of cosmopolitanism, this book explores how Mexican visual culture presents an ongoing process of negotiation between the local and the global.